Seismic behavior of precast concrete beam-column joints with encased steel tube. (1st December 2022) - Lee, Ho-Jun; Park, Hong-Gun
Abstract: Concrete-encased-and-filled steel tubular (CEFT) columns can be potentially connected to concrete beams as well as steel beams. This study aims to develop a novel precast concrete (PC) construction method connecting the CEFT columns and PC beams. In the proposed method, partial openings were provided in the steel tube to facilitate bar placing and concrete casting at the joint. To investigate the seismic behavior of the proposed connections, cyclic lateral loading tests were performed for cruciform beam-column joints. The test parameters were the opening dimensions, presence of cross-beams, and beam flexural strength. In all test specimens, the beam flexural yielding occurred with limited shear damage at the joint, attaining the deformation capacity of more than 4% drift ratio. However, due to the lack of concrete integrity and the reduction of effective joint depth, bond-slip of the beam flexural reinforcement was considerable. The overall seismic performance of the test specimens was evaluated by the acceptance criteria of ACI 374.1-05. While the requirements of the strength and energy dissipation were satisfied, the stiffness requirement was hardly met. On the basis of the results, design considerations for the proposed connection method were recommended. Highlights: Connection details studied for precast concrete beam-to-CEFT column joints. Detailed description and discussion of cyclic lateral loading tests for interior beam-column joints. Shear strength of composite joints evaluated based on current design codes. Design considerations recommended for seismic performance of proposed connections.